Exploring the landscape of adult autism research in psychology: a bibliometric and network analysis - Mota, Fabio Batista; Braga, Luiza Amara Maciel; Cabral, Bernardo Pereira (Frontiers in Psychology, 2024)
The global prevalence of autism spectrum disorder (ASD) is increasing. ASD manifests with persistent social communication and interaction challenges, limited interests, and repetitive behaviors. As the scientific literature on ASD in adults varies greatly, mapping the recent global research becomes valuable for enhancing comprehension of this subject. This study aims to map recent global scientific publications on ASD in adults. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, bibliometrics, and network analyses, we assessed 850 articles indexed in the Web of Science Core Collection between 2013 and 2022 assigned to the research area of psychology. Findings indicate an annual average growth of 11.69%.